The Influence of Emotional and Rational Motives on Decision Making in Choosing Bank Syariah Indonesia Savings Products - Miftakhul Jannah; Muhammad Dandy Alif Wildana (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
This study aims to determine the influence of emotional motives and rational motives in choosing Bank Syariah Indonesia savings products. The method used in this study is quantitative with the Partial Least Square Structural Equation Model or PLS-SEM data analysis method operated through the SmartPLS 4.0 program. As for the data sources used in this study are primary data and the population in this study is the Working Age Population (PUK) in Malang Raya. The sampling technique uses the Purposive sampling method with data collection techniques using questionnaires and utilizing the Likert scale model. The results of the analysis show that the variables of social status, security, comfort and benefits have a positive and significant effect on customer decision making in choosing Bank Syariah Indonesia savings products. This study will contribute to the knowledge that already exists in the literature, especially in the context of factors that influence customer decision making in Bank Syariah Indonesia in the Malang Raya area. Abstrak Penelitian ini bertujuan untuk mengetahui pengaruh motif emosional dan motif rasional dalam memilih produk tabungan Bank Syariah Indonesia. Metode yang digunakan dalam penelitian ini adalah kuantitatif dengan metode analisis data Partial Least Square Structural Equation Model atau PLS-SEM yang dioperasikan melalui program SmartPLS 4.0. Adapun sumber data yang digunakan dalam penelitian ini adalah data primer dan populasi dalam penelitian ini adalah Penduduk Usia Kerja (PUK) di Malang Raya. Teknik pengambilan sampel menggunakan metode Purposive sampling dengan teknik pengumpulan data menggunakan kuesioner dan memanfaatkan model skala likert. Hasil analisis menunjukkan bahwa variabel status sosial, keamanan, kenyamanan dan manfaat berpengaruh positif dan signifikan terhadap pengambilan keputusan nasabah dalam memilih produk tabungan Bank Syariah Indonesia. Penelitian ini akan menambah pengetahuan yang telah ada pada literatur khususnya dalam konteks faktor-faktor yang mempengaruhi pengambilan keputusan nasabah Bank Syariah Indonesia wilayah Malang Raya.